La expresión dramática como estrategia para el desarrollo de la identidad social y cultural en la primera infancia. Una revisión del estado del arte (2019)
The present work, is a state of art, which aims to explore what has been written about the dramatic expression as a strategy for the development of social and cultural identity in childhood between 2012 and 2018, following public policy in early childhood in Colombia, which has focused on the integral development of children, whose purposes of development and learning are: the construction of identity in relation to others, active communication and exploration of the world. For the realization of the state of art, the concepts of childhood, dramatic expression and social and cultural identity are initially defined; Next, a review is carried out in research carried out in Spain, Montenegro, Nicaragua and in some countries of South America such as Ecuador, Peru, Chile and Colombia and are systematized in a research matrix; the convergences and divergences found in the researches explored with respect to research interest are analyzed and conclusions and recommendations are made about the uses of dramatic expression as a strategy for the development of social and cultural identity in early childhood, which allows a close-open for new investigations